Effectiveness of a Game Based Assessment Model for Measuring Character Makeup Skills in Elementary Education - Putri Sarah, Ririn Amaliah; Desri, Widia Permata; Afriyenti, Afriyenti; Fitri, Nabila Aida; Mutiara, Rahmi; Zahratunnisa, Aulia; Ariastuti, Idun (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2026)
This study aimed to develop and evaluate the effectiveness of a game-based assessment model to measure character makeup skills among elementary school students. The model was designed to provide authentic assessment capable of capturing students’ creative processes in an engaging and objective manner, aligned with the learning habits of digital-native learners. The study employed a one group pretest posttest experimental design involving fifth-grade students at SD Negeri 14 Padang Panjang. Data were collected using validated performance rubrics, game learning analytics, classroom observations, and student activity logs, then analyzed with descriptive statistics and paired-samples t-tests. The results indicated a significant improvement in student performance, with mean pretest scores of 63.29 increasing to 82.35 on the posttest (t = 15.842, p = 0.000). Engagement indicators showed high enthusiasm (85.4%), strong focus (68.7%), positive interactions (79.1%), and low confusion (14.5%). System analysis revealed 87.5% instruction following accuracy, a 95.8% task completion rate, and only 4.1% technical errors. These findings confirm that the gamification model effectively enhances creativity, fine motor coordination, color accuracy, and visual instruction-following skills, providing an interactive, motivating, and competency-oriented alternative to assessment in elementary arts education.